Is the impact of environmental regulation on enterprise green technology innovation incentives or inhibitions? A re-examination based on the China meta-analysis - Ren, Gaofei; Chen, Yaoyao (Frontiers in Environmental Science, 2023)
Environmental regulation and green technology innovation are the important driving forces to realize the peak of carbon and carbon neutralization strategy. However, the existing literature on environmental regulation and green technology innovation has not yet reached a consistent conclusion. Based on 39 independent research papers published from 2006 to 2020, this paper integrates and analyzes the relationship between environmental regulation and enterprise green technology innovation and its corresponding dimensions in the context of China. The results show that there is a significant positive correlation between environmental regulation and enterprise green technology innovation overall, and there is a significant positive correlation between command and control environmental regulation, tax-based environmental regulation, enterprise green product innovation, green process innovation, and green R&D investment, but there are differences in intensity. The types of environmental regulation, industry characteristics, and economic regions moderate the relationship between environmental regulation and enterprise green technology innovation. The research results provide new supporting evidence for Porter's hypothesis, further clarify the differences of understanding on the relationship between environmental regulation and enterprise green innovation, and have important reference significance for countries to optimize environmental regulation policies to promote high-quality economic development.